2001
DOI: 10.1086/323277
|View full text |Cite
|
Sign up to set email alerts
|

Goldfields Revisited: A Molecular Phylogenetic Perspective on the Evolution of Lasthenia (Compositae: Heliantheae sensu lato)

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. The University of Chicago Press is collaborating with JSTOR to digitize, preserve and extend access to International Journal of Plant Sciences. DNA sequence data from the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 36 publications
3
57
0
Order By: Relevance
“…A recent phylogenetic study (Chan et al, 2001) shows a close relationship between the two species, but does not conclusively support Ornduff's (1966) and Crawford et al's (1985) proposed ancestordescendent relationship. Nevertheless, the close relationship between the two species is reflected by the high fertility of artificial crosses (Ornduff, 1966).…”
Section: Case Studies Of Endemismmentioning
confidence: 85%
See 1 more Smart Citation
“…A recent phylogenetic study (Chan et al, 2001) shows a close relationship between the two species, but does not conclusively support Ornduff's (1966) and Crawford et al's (1985) proposed ancestordescendent relationship. Nevertheless, the close relationship between the two species is reflected by the high fertility of artificial crosses (Ornduff, 1966).…”
Section: Case Studies Of Endemismmentioning
confidence: 85%
“…ex Lindl. and L. gracilis (DC) Greene (Chan et al, 2001(Chan et al, , 2002. Previous research had shown that there are two edaphic races within this complex, with one race (A) occupying ionically extreme soils such as serpentinite outcrops, coastal bluffs, alkaline flats, and the other (C), occupying ionically moderate yet waterstressed soils (Rajakaruna and Bohm, 1999).…”
Section: Case Studies Of Endemismmentioning
confidence: 99%
“…Race A grows on ionically extreme habitats such as coastal bluffs, alkaline flats, vernal pools, and serpentine soil, while race C is found on ionically benign and drier locations such as pastures and oak woodlands. Phylogenetic analyses using ribosomal and chloroplast sequences along with allozyme variation indicate two cryptic clades within the species with representatives of both races in each [81][82][83][84], suggesting a parallel origin of each race. Greenhouse experiments indicate that race A plants, regardless of phylogenetic clade, have greater tolerance to Na + and Mg 2+ and in drought conditions race C plants flower earlier and produce more flower heads [85,86].…”
Section: A11 Eucalyptus Globulusmentioning
confidence: 95%
“…Lasthenia californica has strong evidence for parallel evolution of two races that have different flavonoid pigments and are found in different edaphic environments using phylogenetic analyses of ribosomal and chloroplast sequence and allozyme variation [81][82][83][84]. Race A is more tolerant of Na + and Mg 2+ and race C flowers earlier and produced more seed heads under drought conditions [85,86].…”
Section: Other Promising Cases Include Lasthenia Californica [81] (Apmentioning
confidence: 99%
“…L. californica was chosen for this study for its self-incompatibility and strong reliance on animals for pollination (Chan et al, 2011). Its range stretches from southern Oregon to southern California and is frequently found in wetland and prairie habitats.…”
Section: Methodsmentioning
confidence: 99%